Modeling and optimization of lipase-catalyzed partial hydrolysis for diacylglycerol production in packed bed reactor - Phuah, Eng Tong; Lee, Yee Ying; Tang, Teck Kim; Lai, Oi Ming; Choong, Thomas Shean Yaw; Tan, Chin Ping; Ng, Wee Nak; Lo, Seong Koon (Walter de Gruyter GmbH, 2016)
Response surface methodology (RSM) was employed to optimize the process variables namely packed bed height (cm) and flow rates (ml/min) on diacylglycerol (DAG) production via partial hydrolysis of palm oil using immobilized Rhizomucor miehei lipase in packed bed reactor (PBR). Quadratic models were successfully developed for both DAG(y) and unhydrolyzed triacylglycerol ((un)TAG) with determination coefficient (R2) of 0.9931 and 0.9986, respectively coupled with insignificant lack of fit (p > 0.05). Optimal conditions for DAG synthesis were evaluated to be 10 cm packed bed height and 3.8 ml/min flow rate. Immobilized enzyme can be reused up to 10 times without significant changes in enzymatic activity. The partial hydrolysis under studied was found to be mass transfer-controlled.